Bone Morphogenetic Proteins Induce Astroglial Differentiation of Oligodendroglial–Astroglial Progenitor Cells - Mabie, P. C. (J Neurosci, 1997)
We have used bipotent postnatal cortical oligodendroglial-astroglial progenitor cells (O-2As) to examine the role of inductive signals in astroglial lineage commitment. O-2A progenitor cells undergo progressive oligodendroglial differentiation when cultured in serum-free medium, but differentiate into astrocytes in medium supplemented with FBS. We now report that the bone morphogenetic proteins (BMPs), a major subclass of the transforming growth factor β (TGFβ) superfamily, promote the selective, dose-dependent differentiation of O-2As into astrocytes with concurrent suppression of oligodendroglial differentiation. This astroglial-inductive action is not sanctioned by other members of the TGFβ superfamily. Astroglial differentiation requires only very brief initial exposure to the BMPs and is accompanied by increased cellular survival and accelerated exit from cell cycle. Dual-label immunofluorescence microscopy documents that O-2A progenitor cells express a complement of BMP type I and type II receptor subunits required for signal transduction. Furthermore, expression of BMP2in vivo reaches maximal levels during the period of gliogenesis. These results suggest that the BMPs act as potent inductive factors in postnatal glial lineage commitment that initiate a stable program of astroglial differentiation.